Transmission and reflection loss measurements for indoor environments at 26 to 40 GHz and 55 to 65 GHz frequency bands - Drozdowska, Monika; Ambroziak, Sławomir J.; Cwalina, Krzysztof K.; Rajchowski, Piotr; Cardona, Narcis (International Journal of Electronics and Telecommunications, 2026)
This paper presents an empirical investigation of the propagation characteristics of common indoor materials, focusing on transmission and reflection losses in two frequency ranges: 26–40 GHz (Ka-band) and 55–65 GHz (V-band). As the development of 5G and future 6G networks moves towards millimetrewave frequencies, understanding the interaction between radio waves and elements of the office environment, such as furniture and structural components, becomes essential for reliable system deployment. The results indicate that while transmission loss increases significantly at higher measured frequencies, the mean reflection loss remains relatively stable across both investigated bands. However, the instantaneous reflection characteristics exhibit significant fluctuations, particularly at lower measured frequencies. The paper identifies materials with dominant blocking or reflecting properties, providing a set of empirical parameters for indoor channel modelling. These findings are instrumental for engineers designing high-capacity indoor wireless networks and precision localisation systems, offering a quantitative basis for link budget calculations in complex indoor scenarios.